Nanocrystalline Diamond as a Coating for Joint Implants: Cytotoxicity and Biocompatibility Assessment. (13th July 2008) - Amaral, Margarida; Gomes, Pedro S.; Lopes, Maria A.; Santos, José D.; Silva, Rui F.; Fernandes, Maria H.
Abstract : Nanocrystalline diamond (NCD) coatings combine a very low surface roughness with the outstanding diamond properties, such as superlative hardness, low self-friction coefficient, high wear and corrosion resistance, and biotolerance, which are ideal features for applications in medicine (knee and hip replacement) and surgical tools. The present work presents a comprehensive study of the cytotoxicity and biocompatibility of NCD films grown by hot-filament chemical vapour deposition (HFCVD) technique, aiming such future applications. Cytotoxicity was evaluated in vitro by seeding human gingival fibroblasts on the NCD surface for 14 days, while specific biocompatibility was assessed on samples seeded with human bone marrow-derived osteoblasts during 21 days. The NCD coatings proved to be noncytotoxic in the preliminary human gingival fibroblast cell cultures, as denoted by a notable sequence of cell attachment, spreading, and proliferation events. In the specific biocompatibility assay envisaging bone tissue applications, NCD coatings induced human osteoblast proliferation and the stimulation of differentiation markers, compared to standard polystyrene tissue culture plates.